The Encyclopedia of Sharks - Parker, Steve (London A & C Black Publishers Ltd, 2011)
The Encyclopedia of Sharks is an up-to-date account of the world's most primitive and feared predators.
Include Color Illustration, Glossary and Index
Keywords: Sharks -- Sharks--Behavior